ANALISIS ASPEK FONETIK DAN FONEMIK BAHASA DAYAK DUSUN TUMBANG DESA MAGALAU HULU KECAMATAN KELUMPANG BARAT KABUPATEN KOTABARU - Husni Mubarak (STKIP Paris Barantai, 2014)
ABSTRACT Phonetic aspect is a branch of linguistics that studies the sounds of language. Thus, in a study entitled